The influence of the "Chef's Table" program on NET TV on culinary creativity knowledge. - Bagus Kuncoro (DIGICOM : Jurnal Komunikasi dan Media, 2023)
In Indonesia, television is considered more dominant than other mass media, such as radio, newspapers and magazines. Television as a source of news has gained enormous trust from the public (90%). Television also has programs or also known as "broadcasts" which are defined as messages or series of messages presented in various forms. So, the definition of a program is everything that is displayed by a broadcasting station to meet the needs of its audience. The Chef's Table program is a cooking show program hosted by a chef and aired on NET TV. This program demonstrates how to cook with a different concept from other cooking programs and visuals that spoil the eyes of the audience while educating. Researchers want to know whether there is an effect of watching the Chef's table program on knowledge of cooking creations in adolescents in RW 13 RT 01 Manukan Kulon, Surabaya. This research is a quantitative study using the theory of uses and gratification related to the influence of the Chef's Table program on NET TV on knowledge of cooking creations in adolescents in RW 13 RT 01 Manukan Kulon, Surabaya. From the results of the study, the data prove that the Chef's Table program has a strong effect on increasing knowledge of cooking creations for the majority of respondents whose frequency and duration of viewing are classified as high.